3D hydrogel-based microcapsules as an in vitro model to study tumorigenicity, cell migration and drug resistance. - Ertekin, Özlem; Monavari, Mahshid; Krüger, René; Fuentes Chandia, Miguel Angel; Parma, Beatrice; Letort, Gaelle; Tripal, Philipp; Boccaccini, Aldo R.; Boßerhoff, Anja Katrin; Ceppi, Paolo; Kappelmann-Fenzl, Melanie; Leal-Egaña, Aldo (Acta Biomaterialia, 2022)
In this work, we analyzed the reliability of alginate-gelatin microcapsules as artificial tumor model. These tumor-like scaffolds are characterized by their composition and stiffness (∼25 kPa), and their capability to restrict -but not hinder- cell migration, proliferation and release from confinement. Hydrogel-based microcapsules were initially utilized to detect differences in mechano-sensitivity between MCF7 and MDA-MB-231 breast cancer cells, and the endothelial cell line EA.hy926. Additionally, we used RNA-seq and transcriptomic methods to determine how the culture strategy (i.e. 2D v/s 3D) may pre-set the expression of genes involved in multidrug resistance, being then validated by performing cytotoxicological tests and assays of cell morphology. Our results show that both breast cancer cells can generate elongated multicellular spheroids inside the microcapsules, prior being released (mimicking intravasation stages), a behavior which was not observed in endothelial cells. Further, we demonstrate that cells isolated from 3D scaffolds show resistance to cisplatin, a process which seems to be strongly influenced by mechanical stress, instead of hypoxia. We finally discuss the role played by aneuploidy in malignancy and resistance to anticancer drugs, based on the increased number of polynucleated cells found within these microcapsules. Overall, our outcomes demonstrate that alginate-gelatin microcapsules represent a simple, yet very accurate tumor-like model, enabling us to mimic the most relevant malignant hints described in vivo, suggesting that confinement and mechanical stress need to be considered when studying pathogenicity and drug resistance of cancer cells in vitro. STATEMENT OF SIGNIFICANCE: In this work, we analyzed the reliability of alginate-gelatin microcapsules as an artificial tumor model. These scaffolds are characterized by their composition, elastic properties, and their ability to restrict cell migration, proliferation, and release from confinement. Our results demonstrate four novel outcomes: (i) studying cell migration and proliferation in 3D enabled discrimination between malignant and non-pathogenic cells, (ii) studying the cell morphology of cancer aggregates entrapped in alginate-gelatin microcapsules enabled determination of malignancy degree in vitro, (iii) determination that confinement and mechanical stress, instead of hypoxia, are required to generate clones resistant to anticancer drugs (i.e. cisplatin), and (iv) evidence that resistance to anticancer drugs could be due to the presence of polynucleated cells localized inside polymer-based artificial tumors.

3D Spheroids Versus 3D Tumor-Like Microcapsules: Confinement and Mechanical Stress May Lead to the Expression of Malignant Responses in Cancer Cells - Fuentes-Chandía, Miguel; Vierling, Andreas; Kappelmann-Fenzl, Melanie; Monavari, Mahshid; Letort, Gaelle; Höne, Lucas; Parma, Beatrice; Antara, Sharmin Khan; Ertekin, Özlem; Palmisano, Ralf; Dong, Meng; Böpple, Kathrin; et al. (Advanced Biology, 2021)
As 2D surfaces fail to resemble the tumoral milieu, current discussions are focused on which 3D cell culture strategy may better lead the cells to express in vitro most of the malignant hints described in vivo. In this study, this question is assessed by analyzing the full genetic profile of MCF7 cells cultured either as 3D spheroids-considered as “gold standard” for in vitro cancer research- or immobilized in 3D tumor-like microcapsules, by RNA-Seq and transcriptomic methods, allowing to discriminate at big-data scale, which in vitro strategy can better resemble most of the malignant features described in neoplastic diseases. The results clearly show that mechanical stress, rather than 3D morphology only, stimulates most of the biological processes involved in cancer pathogenicity, such as cytoskeletal organization, migration, and stemness. Furthermore, cells entrapped in hydrogel-based scaffolds are likely expressing other physiological hints described in malignancy, such as the upregulated expression of metalloproteinases or the resistance to anticancer drugs, among others. According to the knowledge, this study represents the first attempt to answer which 3D experimental system can better mimic the neoplastic architecture in vitro, emphasizing the relevance of confinement in cancer pathogenicity, which can be easily achieved by using hydrogel-based matrices.
CRIS-Team Scopus Importer:2021-05-28
Keywords: 3D cancer models; 3D cell culture; biomaterials for cancer research; solid stress; tumor-like microcapsules

Aflatoxin-specific monoclonal antibody selection for immunoaffinity column development - Ertekin, Özlem; Kaymak, Tuğrul; Pirinçci, Şerife Şeyda; Akçael, Esin; Öztürk, Selma (Biotechniques, 2019)
Antibodies are the basic components of immunoanalytical systems used for detection of a wide range of analytes. Although there are some ground rules for antibody selection, analyte- and assay-specific criteria are the ones that determine the ultimate success of the immunoassays. In this study, we introduced an effective antibody selection procedure for the development of immunoaffinity columns for aflatoxins. The designed scheme puts emphasis on solvent- and matrix-related characterization steps and was used to comparatively evaluate eight monoclonal antibodies. The selected antibody was tolerant to 40% methanol, 20% acetonitrile, 30% acetone and 40% ethanol and did not interact with corn, red pepper or hazelnut extracts. Immunoaffinity columns developed with the selected antibody were validated by 15 independent aflatoxin analysis laboratories.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Antibody selection; Immunoaffinity column; Matrix interference; Mycotoxin analysis; Solvent tolerance

Topical systems for the controlled release of antineoplastic Drugs: Oxidized Alginate-Gelatin Hydrogel/Unilamellar vesicles - Stagnoli, Soledad; Garro, Cintia; Ertekin, Özlem; Heid, Susanne; Seyferth, Stefan; Soria, Gastón; Mariano Correa, N.; Leal-Egaña, Aldo; Boccaccini, Aldo R. (Journal of Colloid and Interface Science, 2023)
The efficacy of chemotherapeutic procedures relies on delivering proper concentrations of anti-cancer drugs in the tumor surroundings, so as to prevent potential side effects on healthy tissues. Novel drug carrier platforms should not just be able to deliver anticancer molecules, but also allow for adjustements in the way these drugs are administered to the patients. We developed a system for delivering water-insoluble drugs, based on the use of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), or bis(2-ethylhexyl) sulfosuccinate benzyl-n-hexadecyldimethylammonium (BHD-AOT), embedded into oxidized alginate-gelatin (ADA/Gel) hydrogel, emulating a patch for topic applications. After being loaded with curcumin, cancer cells such as human colorectal adenocarcinoma (HCT116 and DLD-1) and melanoma cell lines (MEL501), and non-malignant cells such as mammary epithelial cell lines (NMuMG) and embryonal fibroblasts (NIH 3T3 or NEO cells) were analyzed for biocompatibility and cytotoxic effects. The results show that the proposed system can load comparatively higher concentrations of the drug (with respect to other nano/microcarriers in the literature), and that it can enhance the likelihood of the drug being uptaken by cancer cells instead of non-malignant cells. These assays were complemented by diffusion studies across the stratum corneum of rat skin, with the aim of determining the system's efficiency during topical application. Finally, the stability of the patch was tested after lyophilization to determine its potential pharmaceutical use. As a whole, the combined system represents a highly reliable and robust method for embedding and delivering complex insoluble chemotherapeutical molecules, and it is less invasive than other alternative methods in the literature.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Controlled antineoplastic drug release; Hydrogel; Nanocarriers; Topical drug delivery system